Analisis Kualitas Website GuruInovatif.id Menggunakan Pendekatan WebQual dan Importance Perfomance Analysis (IPA) - Pusung, Yearsky Lifael; Setiawan, Eman (STMIK Dharmapala Riau, 2024)
The impact of technology, especially the internet, on human life, including the business sector, has been significant. Websites are now essential for providing information, promoting products/services, and communicating with customers. This study evaluates the quality of the Kaskus website using the WebQual method, which assesses usability, information, and service interaction. The Importance-Performance Analysis (IPA) method is used for a descriptive analysis. The findings indicate that the GuruInovatif.id Platform falls short of user expectations, with a negative Average Gap Score (GAP) of -0.41. To address this, improvements should be made to relevant indicators and attributes. The study concludes that the perceived quality of the GuruInovatif.id Platform does not meet user expectations, especially in terms of information attributes. Therefore, it is important to prioritize enhancing the level of detail in information. This research aims to assist the management team of GuruInovatif.id in improving service quality, remaining competitive, and meeting community needs and expectations.